BIODIESEL NO BRASIL: MATÉRIAS PRIMAS E TECNOLOGIAS DE PRODUÇÃO - Tapanes, Neyda de la Caridad Om; Aranda, Donato Alexandre Gomes; Perez, Rodolfo Salazar; Cruz, Yordanka Reyes (Acta Scientiae et Technicae; v. 1 n. 1 (2013): I Simpósio de Biotecnologia e BiodiversidadeDO - 10.17648/uezo-ast-v1i1.11, 2013)
Since the birth of the environmentalist movement, and, specially after the oil crisis in the 70s, alternative forms of energy have been discussed in order to substitute fossil fuels. One of these alternative fuels, Biodiesel, had its production and consume determined in the form of the law 11.097/05. In this paper, we discuss the current state of the art of Biodiesel in Brazil.